2019
DOI: 10.1080/0886022x.2019.1669460
|View full text |Cite
|
Sign up to set email alerts
|

The miR-15a-5p-XIST-CUL3 regulatory axis is important for sepsis-induced acute kidney injury

Abstract: Background: Acute kidney injury (AKI) refers to a sudden loss of renal function. This study was performed to identify the key RNAs acting in the mechanism of sepsis-induced AKI.Methods: Microarray dataset GSE94717 (including six sepsis-induced AKI samples and three control samples) was downloaded from Gene Expression Omnibus database. Differentially expressed miRNAs (DE-miRNAs) were identified. The miRNA targets were predicted and enrichment analysis was performed. Protein-protein interaction (PPI) and competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Cheng & Wang, 2020). The XIST/miR-15a-5p/CUL3 regulatory axis participates in sepsis-induced AKI (Xu et al, 2019). Here, we found that XIST was upregulated in AKI and knockdown of XIST Recently, accumulating evidence has shown that miR-142-5p is involved in various diseases (Chaudhuri, Yelamanchili, Marcondes, & Fox, 2013;Schaefer, Montufar-Solis, Vigneswaran, & Klein, 2011;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Cheng & Wang, 2020). The XIST/miR-15a-5p/CUL3 regulatory axis participates in sepsis-induced AKI (Xu et al, 2019). Here, we found that XIST was upregulated in AKI and knockdown of XIST Recently, accumulating evidence has shown that miR-142-5p is involved in various diseases (Chaudhuri, Yelamanchili, Marcondes, & Fox, 2013;Schaefer, Montufar-Solis, Vigneswaran, & Klein, 2011;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, when we tested the presence of RNU6-2 in the urine, about half of the urine samples from HSs did not show a Ct < 35 (not shown) and we believe it is risky to normalize miRNAs with a transcript present in the urine at very low levels and with high inter-subject variability, particularly in HSs. Moreover, miR-15a is present at high levels in the blood of patients with acute kidney injury 39 , suggesting that miR-15a may be present at high levels in the urine of patients without cancer but with non-cancerous diseases of the kidney, potentially increasing the false positive rate of the test. Our study suggests that evaluating the amplification of some miRNAs instead of that of one miRNA represents an advantage in patients in which alteration of the urinary presence of just one miRNA occurs for reasons that are not evident in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of XIST and miR-15a-5p enhanced and preserved LPS-induced apoptosis significantly, while the miR-15a-5p inhibitor reversed the renal cell apoptosis. Furthermore, overexpression of the CUL3 gene considerably reduced the LPS and miR-l5a-5p -induced apoptosis [ 57 ]. Another explanation of sepsis pathophysiology is based on regulation of the crucial inflammatory response of damaged organs with the participation of miR-15a-5p .…”
Section: Micrornas Associated With Aki Induced By Sepsis or Nephromentioning
confidence: 99%